Influence of Fluid Ingestion on Heart Rate, Cardiac Autonomic Modulation and Blood Pressure in Response to Physical Exercise: A Systematic Review with Meta-Analysis and Meta-Regression - Porto, Andrey A. [UNESP]; Benjamim, Cicero Jonas R.; da Silva Sobrinho, Andressa Crystine; Gomes, Rayana Loch; Gonzaga, Luana A. [UNESP]; da Silva Rodrigues, Guilherme; Vanderlei, Luiz Carlos Marques [UNESP]; Garner, David M.; Valenti, Vitor E. [UNESP] (MDPI, 2023)
A systematic review was undertaken to investigate the involvement of hydration in heart rate (HR), HR variability (HRV) and diastolic (DBP) and systolic (SBP) blood pressure in response to exercise. Data synthesis: The EMBASE, MEDLINE, Cochrane Library, CINAHL, LILACS and Web of Science databases were searched. In total, 977 studies were recognized, but only 36 were included after final screening (33 studies in meta-analysis). This study includes randomized controlled trials (RCTs) and non-RCTs with subjects > 18 years old. The hydration group consumed water or isotonic drinks, while the control group did not ingest liquids. For the hydration protocol (before, during and after exercise), the HR values during the exercise were lower compared to the controls (−6.20 bpm, 95%CI: −8.69; −3.71). In the subgroup analysis, “water ingested before and during exercise” showed lower increases in HR during exercise (−6.20, 95%CI: 11.70 to −0.71), as did “water was ingested only during exercise” (−6.12, 95%CI: −9.35 to −2.89). Water intake during exercise only revealed a trend of avoiding greater increases in HR during exercise (−4,60, 95%CI: −9.41 to 0.22), although these values were not significantly different (p = 0.06) from those of the control. “Isotonic intake during exercise” showed lower HRs than the control (−7.23 bpm, 95% CI: −11.68 to −2.79). The HRV values following the exercise were higher in the hydration protocol (SMD = 0.48, 95%CI: 0.30 to 0.67). The values of the SBP were higher than those of the controls (2.25 mmHg, 95%CI: 0.08 to 4.42). Conclusions: Hydration-attenuated exercise-induced increases in HR during exercise, improved autonomic recovery via the acceleration of cardiac vagal modulation in response to exercise and caused a modest increase in SBP values, but did not exert effects on DBP following exercise.
Keywords: autonomic nervous system; cardiovascular physiology; dehydration; electrolyte balance; heart rate control; water intake